Improving fault traceability of web application by utilizing software revision information and behavior model - Baek, Seungsuk; Lee, Jung Won; Lee, Byungjeong (KSII Transactions on Internet and Information Systems, 2018)
Modern software, especially web-based software, is broadly used in various fields. Most web applications employ design patterns, such as a model-view-controller (MVC) pattern and a factory pattern as development technology, so the application can have a good architecture to facilitate maintenance and productivity. A web application, however, may have defects and developers must fix the defects when a user submits bug reports. In this paper, we propose a novel approach to improving fault traceability in web application by using software revision information and software behavior model to reduce costs and effectively handle the software defect. We also provide a case study to show effectiveness of our approach.
Keywords: Behavior model; Design Patterns; Development technology; Model view controller; Software behavior; Software revisions; WEB application; Web-based softwares; Behavior model; Design pattern; Fault traceability; Software revision information; Web application